The 3in1 Robot Design for Medical Assistant on 2019-nCoV case - Syamsiar Kautsar; Robby Ardiansyah; Muhammad Mashfuks; Khafidurrohman Agustianto (Indonesian Journal of Engineering Research, 2021)
Covid-19 (Coronavirus disease 2019) is a new coronavirus (SARS-CoV-2) that is known to have originated in Wuhan, China. It was found at the end of December 2019 with countries infected with the Coronavirus in more than 65 countries. According to WHO data as of the 4th of March 2020, the number of sufferers was 90,308 infected with Covid-19. In Indonesia as of April 14, 2010, people with Covid-19 were positive for 4,839, recovered 426, and died 459. In Indonesia, one of the ways to tackle the Covid-19 pandemic is by spraying with disinfectant liquid and delivering food or medicine to patients infected with Covid. -19 is still in close contact with a patient who is still likely to be infected from that patient. According to general guidelines in dealing with the Covid-19 pandemic, one of them is done by spraying disinfectants in several public facilities such as health clinics, government office, schools, bridges, parks, fields, and other public areas. However, sterilization is still done manually by health workers. This puts medical personnel at risk of being exposed to the covid-19 virus. Therefore, in this study, a multi-functional robot with a remote control equipped with an FPV camera was developed. The robot can be used to spray disinfectant, UV lamp-based sterilization, and deliver food and medicine to patients infected with Covid-19. From the test results, the teleoperation system can work well with a range of 30 meters indoors and 150 meters outdoors.